Effects of different biomass substrates on the adsorption of anti-inflammatory and caffeine - Celine, Chong Xiu Ying (2025)
Emerging contaminants, such diclofenac and caffeine, provide huge problems for the environment because of their long-term persistence and bioactivity. Conventional wastewater treatment technologies inadequately eliminate these contaminants, necessitating new alternatives. The study investigates the adsorption capacity and efficiency of biochar produced from sugarcane, rice straw, and corn cob, in conjunction with zeolite, as sustainable adsorbents. And examine the effect of physicochemical characteristics and determine the most suitable substrate for the treatment of wastewater. The substrates were analyzed by Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and Brunauer-Emmett-Teller (BET) analysis to assess functional groups, surface shape, and porosity. Batch adsorption experiments assessed pollutant removal efficiency at different concentrations. The BET surface area of the analyzed biochar sample is moderately high, making it appropriate for adsorption applications involving big molecules. Zeolite is optimal for the adsorption of little molecules. FTIR data indicated the existence of hydroxyl and carbonyl groups on biochar, hence improving adsorption efficacy. The adsorption of Diclofenac indicates that all substrates have effectively eliminated the micropollutants. Research indicates that charcoal substrates outperform zeolite in relation to caffeine. The results indicated that biochar exceeded zeolite in both adsorption capacity and efficiency, with sugarcane biochar identified as the most effective substrate. The study highlights the viability of utilizing biochars obtained from agricultural waste as economical and environmentally beneficial options for large-scale wastewater treatment, hence aiding sustainable environmental management. Additional research is advised to enhance the scalability and regeneration of these adsorbents.